Uncommon halogen bond motifs in cocrystals of aromatic amines and 1, 4-diiodotetrafluorobenzene. Issue 39 (30th August 2016) - Nemec, Vinko; Cinčić, Dominik
Abstract : A number of novel halogen-bonded aromatic amine cocrystals with 1, 4-diiodotetrafluorobenzene have been synthesized via both mechanochemical and solution syntheses, offering valuable insight into potential halogen bond acceptor species. Abstract : A number of novel halogen-bonded aromatic amine cocrystals with 1, 4-diiodotetrafluorobenzene have been synthesized via both mechanochemical and solution syntheses, offering valuable insight into potential halogen bond acceptor species.